Association of Urinary Phytoestrogens With Pelvic Organ Prolapse and Fecal Incontinence Symptoms in Postmenopausal Women. Issue 2 (March 2019) - Cardenas-Trowers, Olivia; Meyer, Isuzu; Richter, Holly E.; Addis, Ilana; Markland, Alayne D.
Abstract : Objectives: The aim of this study was to investigate the association between urinary phytoestrogen levels with symptoms of pelvic organ prolapse (POP) and fecal incontinence (FI) in postmenopausal women. Methods: This is a cross-sectional study using the National Health and Nutrition Examination Survey database from 2005 to 2010 including postmenopausal women 40 years or older who either had both ovaries removed and/or had no period in the past year due to hysterectomy and/or menopause. Urinary concentrations of 6 phytoestrogens were measured. Pelvic organ prolapse symptoms were defined as a positive response to the question, "Do you see or feel a bulge in the vaginal area?" Fecal incontinence was defined as leakage of mucus, liquid, or solid stool occurring at least monthly. Using appropriate sample weights, prevalence estimates and 95% confidence intervals were calculated. Logistic regression was performed assessing associations between pelvic floor symptoms and log-transformed phytoestrogen levels adjusting for appropriate covariates. Results: Participants included 1341 postmenopausal women with phytoestrogen data; 1213 with or without POP symptoms and 1221 with or without FI symptoms. Multivariable analysis revealed no association of urinary phytoestrogen levels with POP symptoms. Higher urinary O-desmethylangolensin level was associated with decreased odds of FI symptoms in postmenopausal women (adjusted odds ratio, 0.92; 95% confidence interval, 0.86–0.99). Conclusions: Increased urinary O-desmethylangolensin level was associated with lower odds of FI. Future research may be warranted to further investigate the potential of specific phytoestrogens as mediators of FI, as well as the role of phytoestrogens on POP symptoms.